О других деятелях отечественной микробиологии: Д.К.Заболотный, М.А.Морозов, С.И.Златогоров и Л.В.Громашевский - Дубровинський, С.Б. (Сумський історико-архівний журнал, 2010)
One fragment of the professor Samuil Borisovich Dubrovinsky’s recollection (1885-
1975), devoted to the outstanding microbiologists and epidemiologists Daniil Kirillovich
Zabolotny (1866-1929), Semyon Ivanovich Zlatogorov (1873-1931) and Mikhail Akimovich
Morozov (1879-1964), Lev Vasilyevich Gromashevsky (1887-1980), was published for the
first time. K.K.Vasylev’s comments.